Micro-level prediction of outstanding claim counts based on novel mixture models and neural networks - Axel Bücher; Alexander Rosenstock (European Actuarial Journal, 2022)
Predicting the number of outstanding claims (IBNR) is a central problem in actuarial loss reserving. Classical approaches like the Chain Ladder method rely on aggregating the available data in form of loss triangles, thereby wasting potentially useful additional claims information. A new approach based on a micro-level model for reporting delays involving neural networks is proposed. It is shown by extensive simulation experiments and an application to a large-scale real data set involving motor legal insurance claims that the new approach provides more accurate predictions in case of non-homogeneous portfolios.
Keywords: 510; Loss reserving; Individual claim features; General insurance; Randomly truncated data; Expectation maximization algorithm; Mixture distribution